Two new chasmophytic species of Silene (Caryophyllaceae, sect. Siphonomorpha) from Iran - Jafari, Farzaneh; Keshavarzi, Maryam; Doostmohammadi, Moslem; Mirtadzadini, Mansour (European Journal of Taxonomy, 2023)
Based on morphological and molecular evidence, two new species of Silene are recognized and described here, S. penduliflora F.Jafari, Keshavarzi & Doostm. sp. nov. and S. thyrsiantha F.Jafari, Mirtadz. & Keshavarzi sp. nov. The newly discovered species are distributed in the central and southeastern parts of Iran, growing in rocky habitats. Relationships among these species and their close relatives are demonstrated using nrDNA ITS and cpDNA rps16 phylogenies. Silene ghahremaninejadii, S. parrowiana, and S. shahrudensis form a clade with these new species. A key to S. penduliflora and S. thyrsiantha and their close relatives is provided.